Reproductive Toxicity of the Fungicide Remilitine, Chromium Ions, and Their Mixture in the Earthworm Eisenia fetida - Aebeed S. Aebeed; Salaheddin A. Sharif; Abeer H. Amer (African Journal of Advanced Pure and Applied Sciences, 2026)
The widespread use of pesticides and heavy metals raises concerns about their long‑term impacts on soil ecosystems. This study evaluated the sub‑lethal reproductive effects of chromium (200 ppm) and the fungicide Remilitine (500 ppm), individually and in combination, on the earthworm Eisenia fetida. Adult worms were cultured in artificial soil and exposed for 70 days. Cocoon production was assessed at 28 and 70 days, while juvenile numbers were recorded at day 70. Statistical analysis revealed that Remilitine significantly reduced cocoon production compared to controls at 28 days, whereas chromium alone had no significant effect. By day 70, cocoon numbers in the chromium–Remilitine group were comparable to controls, indicating recovery. However, juvenile numbers were consistently reduced across all treated groups, with the mixture showing an antagonistic effect. These findings highlight the importance of evaluating mixture toxicity in soil organisms to better understand ecological risks of combined contaminants.